Tinjauan Yuridis Terhadap Upaya Penanggulangan Promosi Judi Online di Instagram di Tinjau dari UU ITE: Penelitian - Reyzha Afrinda Wulandari; Henry Arianto (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study normatively examines Decision Number 509/Pid.Sus/2024/PN Srg of the Serang District Court in the context of eradicating online gambling in Indonesia, using normative legal research methods with a case approach and statute approach. The author analyzes the chronology of the case that began with public reports regarding the activities of online bookies, cumulative charges of Article 27 paragraph (2) in conjunction with Article 45 paragraph (2) of the ITE Law in conjunction with Article 303 of the Criminal Code, the prosecutor's demand for 5 years imprisonment and a fine of Rp. 500 million subsidiary to 6 months, as well as the judge's assessment of promotion via Instagram as the distribution of content that violates morality as proven by electronic evidence, IT expert witnesses, and billions of rupiah in transactions. The role of the government through the Presidential Decree Task Force No. 21/2024, the blocking of the Ministry of Communication and Information, and the synergy of the National Police have proven effective, although the challenges of overseas server jurisdiction and celebrity promotion still exist. The results demonstrate the fulfillment of all elements of a criminal offense (subject, subjective, objective, consequences, lex scripta), the legal certainty of the ITE Law, and a positive precedent for digital law enforcement. The conclusions affirm the success of the normative method in revealing the effectiveness of decisions, with recommendations for revising the ITE Law, training cyber judges, international collaboration, and preventive public education. This research contributes to the development of cybercriminal law doctrine in Indonesia.